Frovatriptan vs. other triptans for the acute treatment of oral contraceptive-induced menstrual migraine: pooled analysis of three double-blind, randomized, crossover, multicenter studies - Allais, G. (Springer Milan, 2013)
Oral contraceptive-induced menstrual migraine (OCMM) is a particularly severe form of migraine triggered by the cyclic hormone withdrawal. To review the efficacy of frovatriptan vs. other triptans, in the acute treatment of OCMM through a pooled analysis of three individual randomized Italian studies. With or without aura migraineurs were randomized to frovatriptan 2.5 mg or rizatriptan 10 mg (study 1), frovatriptan 2.5 mg or zolmitriptan 2.5 mg (study 2), frovatriptan 2.5 mg or almotriptan 12.5 mg (study 3). All studies had a multicenter, randomized, double-blind, crossover design. After treating 1–3 episodes of migraine in 3 months with the first treatment, patients switched to the other treatment for the next 3 months. In this analysis, the subset of 35 of the 280 women of the intention-to-treat population taking combined oral contraceptives and experiencing a migraine attack during the withdrawal phase, were analyzed. The proportion of pain free and pain relief at 2 h were 25 and 51 % with frovatriptan and 28 and 48 % with comparators (p = NS). At 24 h, 71 and 83 % of frovatriptan-treated patients and 60 and 76 % of comparator-treated patients were pain free (p < 0.05 between treatments) and had pain relief (p = NS), respectively. Relapse at 24 and 48 h was significantly (p < 0.05) lower with frovatriptan (17 and 21 %) than with the comparators (27 and 31 %). Our results suggest that, due to its sustained antimigraine effect, frovatriptan may be particularly suitable for the management of OCMM than other triptans.